Evaluation of Antitermite Properties of Wood Extracts from Pongamia pinnata (L.) Pierre (Leguminosae) against Subterranean Termites - AHMED,SOHAIL (2022)
Abstract Termiticide, repellent and antifeedant activities of extracts from Pongamia pinnata wood were evaluated against Coptotermes heimi (Wasmann) at three different concentrations preceded by a preliminary choice and no-choice tests for natural resistance of tested wood. Termites’ mortality was determined in each case of extract and solvent treated Whatman filter paper. Finally, wooden blocks of poplar (19×19×19 mm) were treated with extracts and respective solvents and exposed to termites in the field for 28 days. Minimum mean weight loss was observed in dried P. pinnata (6.38%), followed by fresh P. pinnata in choice tests. In no-choice tests, dried P. pinnata was comparatively resistant with a weight loss of 12.37%, followed by fresh P. pinnata and P. deltoides. In toxicity bioassay, ethyl acetate-based wood extracts caused the highest mortality (41.66%), followed by petroleum ether, hexane, and water extracts at 10 mg/ml concentration. Similarly, ethyl acetate-based extracts showed maximum repellency (100%) followed by petroleum ether extracts at 10 mg/ml and ethyl acetate at 5 mg/ml after 60 min of termite exposure. Minimum wood losses were observed in woods treated with ethyl acetate extracts compared to control and other treatments in field experiments.